PENGARUH MODEL INQUIRY LEARNING TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA SISWA STUDI LITERATUR - Hanura Hanura (Dharmas Education Journal (DE_Journal), 2020)
The problem of this study is the score of Bahasa Indonesia is not optimal yet, this is because learning is monotonous and students are less active, to overcome this problem it was necessary to use an effective learning model to improve student learning outcomes. This type of research is research using literature study of the Inquiry Learning model on student learning outcomes. The data collection technique was obtained from a literature study. This research was conducted by comparing the opinions and research results from references taken by the researcher in this study. From reffering with several sources that the researchers took and quoted had an impact on the learning process and the value of Indonesian which had a significant effect on the Inquiry Learning model on Indonesian language learning in students, this study using literature studies is an Inquiry Learning model in increasing student activity, in increasing motivation student learning, in improving students' critical thinking skills. This research shows that there is an influence of the Inquiry Learning model on student learning outcomes in Bahasa Indonesia.